Bilateral Tubal Ectopic Pregnancy After Assisted Reproduction Technique: A Case Report - Davut Güven; Özgür Erdoğan; İsmail Kılıço; İdris Koçak; Cazip Üstün (Medical Network, 2009)
Ectopic pregnancy is still an important cause of maternal mortality. Bilateral tubal ectopic pregnancy is very rare, and is usually the result of an assisted reproduction technique. We describe a case of early bilateral tubal pregnancy diagnosed by transvaginal ultrasonography after intracytoplasmic sperm injection (ICSI) and embryo transfer (ET).